Unveiling the acetone sensing mechanism by WO3 chemiresistors through a joint theory-experiment approach. (1st March 2021) - Americo, Stefano; Pargoletti, Eleonora; Soave, Raffaella; Cargnoni, Fausto; Trioni, Mario Italo; Chiarello, Gian Luca; Cerrato, Giuseppina; Cappelletti, Giuseppe
Highlights: Synthesis of γ -monoclinic WO 3 by a novel template-mediated sol-gel method. Study of acetone sensing by WO 3 in inert and simulated air to unveil the O 2 role. Density functional theory used to unravel the sensing mechanism by γ − WO 3 . The acetone interaction through carbonyl group releases electrons to WO 3 surface. Balance between simple acetone adsorption and its reaction depending on O 2 presence. Graphical abstract: Abstract: The acetone sensing mechanism by WO 3 was investigated through a combined experimental and theoretical approach. The γ − monoclinic WO 3 powder was synthesized by a template-mediated sol-gel method and characterized on structural, surface, morphological and optical points of view. A thin film of WO 3 was deposited on interdigitated Au electrodes by hot-spray method and tested at 300 ∘ C (while applying a bias of 1.0 V) for acetone gas sensing, both in presence and absence of oxygen in the gas carrier. Interestingly, the absence of oxygen had no significant effect on the sensor response intensity but it dramatically increased the recovery times (from 120 s to 2700 s). In order to explain these experimental results, by means of ab initio density functional theory calculations, we modeled a defective γ − WO 3 surface structure and simulated the adsorption of acetone and oxygen molecules on top of it. We unprecedentedly evidenced that, in presence of surface oxygen vacancies, both acetone adsorption and its oxidation reaction can occur. However, their contribution to the sensor response strictly depends on the inert/oxidative atmosphere present in the sensing chamber, which in turn strongly affects the surface oxygen population. Our findings can either be the guidelines for future studies aimed at delineating the possible reaction products or pave the way for the engineering of tailored nanomaterials having specific surface features and enhanced sensing properties.